Mutation profile of diffuse large B-cell lymphoma with relapses in the central nervous system - E. N. Voropaeva; T. I. Pospelova; V. S. Karpova; M. I. Churkina; Yu. V. Vyatkin; T. A. Ageeva; V. N. Maksimov (Успехи молекулярной онкологии, 2022)
Introduction. The recurrence of diffuse large B-cell cell lymphoma in the central nervous system in the vast majority of cases is a fatal manifestation of the disease. The study of the lymphoma mutational profile can improve the accuracy of the prognosis of relapse in the central nervous system and justify the selection of patients for preventive treatment. Aim. To evaluate the mutational profile of cases of diffuse large B-cell cell lymphoma with central nervous system damage in relapse based on the results of our own experiment on high-performance sequencing.Materials and methods. On the Illumina platform, full-exome sequencing of diagnostic samples of diffuse large B-cell cell lymphoma with relapses in the central nervous system was performed. A panel including more than 70 genes was analyzed.Results. Four main groups of genetic events can be distinguished in the group of studied samples, namely: combined mutations in the NF-kB (MYD88, NOTCH1, CD79B, CARD11) and JAK-STAT (PIM1, STAT6) signaling pathways, as well as aberrations in the main oncosuppressor TP53 and chromatin remodeling system genes (ARID1A, KMT2D, EP300, SMARCA4). A recurrent mutation c. 794T>C, p.L265P MYD88 was detected in the study group. Among other findings, mutations in the CIITA and CD58 genes should be noted, which are important in avoiding tumor cells from immune surveillance.Conclusion. Despite the apparent heterogeneity of the mutational profile of diffuse large B-cell cell lymphoma with relapses in the central nervous system, in most cases, tumor cells were characterized by genetic disorders leading to the production of a large number of pro-inflammatory cytokines by malignant lymphocytes, as well as aberrations that reduce immunogenicity and contribute to the avoidance of immune surveillance by the tumor.